MATERNAL ENGAGEMENT IN A HOME VISITING INTERVENTION: WHAT LIES BENEATH PSYCHOLOGICAL RESOURCES?1. Issue 1 (January 2014) - Booth, Ailbhe; Munsell, Eylin Palamaro; Doyle, Orla
<x xml:space="preserve">Abstract</x> This study examined the factors influencing participant engagement in a home visiting program. Specifically, it explored the relationship between dosage and the constituent components of psychological resources: mental health, mastery, and cognitive resources. Multiple linear regression analyses were conducted utilising implementation data from a sample (n = 95) of participants in an Irish home visiting program. Psychological resources significantly predicted dosage, yet an investigation of each component found that only cognitive resources remained significant. Furthermore, when considering types of cognitive resources, verbal ability was found to significantly predict the number of home visits but not the average duration of visits. Conversely, perceptual reasoning was found to predict the average duration of home visits but not the number of home visits. These results suggest that cognitive resources may be the driving component behind previous findings that link psychological resources and level of dosage in home visiting programs. Practice and policy implications are explored.